Blood culture bottle culture of pleural fluid in pleural infection. Issue 8 (1st April 2011) - Menzies, Sarah M; Rahman, Najib M; Wrightson, John M; Davies, Helen E; Shorten, Robert; Gillespie, Stephen H; Davies, Christopher W H; Maskell, Nick A; Jeffrey, Andrew A; Lee, Y C Gary; Davies, Robert J O
Abstract : Background: Pleural infection is common, and has a >30% major morbidity and mortality—particularly when infection is caused by Gram-negative, Staphylococcus aureus or mixed aerobic pathogens. Standard pleural fluid culture is negative in ∼40% of cases. Culturing pleural fluid in blood culture bottles may increase microbial yield, and is cheap and easy to perform. Objectives: To determine whether inoculating pleural fluid into blood culture bottles increases the culture positivity of pleural infection over standard laboratory culture, and to assess the optimum volume of inoculum to introduce. Methods: 62 patients with pleural infection were enrolled. Pairs of aerobic and anaerobic blood culture bottles were inoculated at the bedside with 2, 5 or 10 ml of pleural fluid, and two pleural fluid specimens were sent for standard culture. Pleural fluid from nine control patients was cultured to test for 'false-positive' results. Results: The addition of blood culture bottle culture to standard culture increased the proportion of patients with identifiable pathogens by 20.8% (20/53 (37.7%) to 31/53 (58.5%) (difference 20.8%, 95% CI difference 8.9% to 20.8%, p<0.001)). The second standard culture did not similarly improve the culture positivity (19/49 (38.8%) to 22/49 (44.9%) (difference 6.1%, 95% CI difference −2.5% to 6.1%, p=0.08)). The culture inoculum volume did not influence bacterial isolation frequency. The control fluids were culture negative. Conclusions: Blood culture bottle culture of infected pleural fluid increases microbial yield when used in addition to standard culture. This technique should be part of routine care.